Preparation method and application of lignin-based hydrogel for adsorbing nitrogen and phosphorus ions
The lignin-based hydrogel prepared by radical polymerization can absorb nitrogen and phosphorus ions simultaneously, solving the problem that the existing technology cannot simultaneously remove anion and cationic pollutants in water bodies, and applying it to the field of rice hydroponics as The sustained release fertilizer achieves efficient removal of nitrogen and phosphorus ions and high-value utilization of lignin.
Patent Information
- Application Number
- CN202411430444.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Existing nitrogen and phosphorus ion adsorption materials cannot simultaneously efficiently remove anion and cationic pollutants from water bodies, and the formaldehyde used in the preparation process is not friendly to the environment and humans and cannot meet the actual application needs.
By conducting free radical polymerization of lignin sulfonate with methacryloyloxyethyltrimethylammonium chloride, acrylic acid, N,N-methylenebisacrylamide and potassium persulfate, nitrogen can be prepared by simultaneously adsorbing and phosphorus ions of lignin-based hydrogels and applied them to the field of rice hydroponics as a sustained release fertilizer.
It realizes efficient adsorption and recovery of nitrogen and phosphorus ions in water, and develops the adsorbed lignin-based hydrogel into a slow-release fertilizer, promotes the growth of rice seedlings, has good application prospects, and provides industrial lignin High-value utilization approach.
Smart Images

Figure BDA0005083508430000081 
Figure HDA0005083508440000011 
Figure HDA0005083508440000012
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a lignin-based hydrogel capable of absorbing nitrogen and phosphorus ions and application thereof, and belongs to the field of functional materials. Background Art
[0002] Resource shortage and environmental pollution are global issues facing mankind today. Phosphorus is an essential nutrient for the survival of all organisms in nature. However, with the rapid development of related industries, a large amount of wastewater containing nitrogen and phosphorus is discharged into the runoff system, causing serious eutrophication of water bodies and posing a serious threat to ecological balance. Therefore, effectively controlling nitrogen and phosphorus pollutants in water bodies and alleviating eutrophication of water bodies has become one of the problems that need to be solved urgently.
[0003] At present, many technologies have been applied to remove nitrogen and phosphorus pollutants from water bodies. Among them, the adsorption method is not only low-cost, simple to operate, fast and efficient, but also can achieve the recovery of nitrogen and phosphorus in water bodies and the recycling of adsorbents through a simple desorption process. It is considered to be one of the technologies with great potential for industrial application. The key to treating nitrogen and phosphorus wastewater by adsorption is to develop cheap, efficient, green and pollution-free adsorption materials. Compared with common activated carbon, carbon nanotubes, porous microspheres, ion exchange resins and metal organic frameworks, the raw materials of biomass-based materials are cheap, easy to obtain and renewable, and are an adsorption material with great potential for industrial application. Among them, lignin is a very abundant type of renewable biomass resource in nature. It not only has a wide range of sources, abundant reserves, renewable, and good environmental compatibility, but also has rich oxygen-containing functional groups. It can be developed into various green and efficient lignin-based adsorbents, which have great application potential in wastewater treatment. At present, according to the type of ions given to the functional groups, lignin-based adsorbents are generally divided into cationic and anionic adsorbents.
[0004] Lignin-based anionic adsorbents are usually prepared by transferring sulfonic acid groups or carboxyl groups on lignin to lignin through sulfonation, carboxymethylation, graft polymerization, etc. At present, there are studies on the adsorption of lignin adsorbents on cationic methylene blue, Congo red, Cr(VI), and Cd in wastewater. 2+The removal effect of lignin is studied. Lignin-based cationic adsorbents are generally prepared by introducing cationic amines or quaternary amino groups to lignin. The amination of lignin has been widely studied through the Mannich reaction, which can transfer amine (e.g., primary amines, secondary amines and tertiary amines) groups to lignin. Various other amines including diethylenetriamine (DETA), polyethyleneimine (PEI), ethylenediamine, etc. are also used in the reaction. However, the amination process requires formaldehyde as a crosslinker, which is not friendly to the environment and humans. Quaternary ammonium groups are usually introduced into lignin through free radical polymerization or etherification. The etherification reaction of lignin is usually completed by reacting the hydroxyl groups in lignin with epoxypropyltrimethylammonium chloride or 3-chloro-hydroxypropyltrimethylammonium chloride under alkaline conditions, which enables the reaction to be carried out in a homogeneous system. The free radical polymerization reaction of lignin is usually carried out with vinyl monomers containing quaternary ammonium groups as monomers, and commonly used monomers include dimethyldiallyl ammonium chloride (DADMAC) or methacryloyltrimethylammonium chloride (METAC). Methacryloyloxyethyl trimethylammonium chloride can polymerize with a large number of free radical sites on the benzene ring of lignin, thereby improving the adsorption capacity of the adsorbent. However, free radical polymerization reactions are usually carried out under acidic conditions. Since ordinary lignin is insoluble in acidic solutions, these reactions are usually carried out in heterogeneous systems, which will affect the reaction efficiency. In addition, it has been confirmed that eutrophic wastewater usually contains both anionic and cationic pollutants. Lignin-based gel adsorbents containing only one ionic group cannot remove all ionic pollutants and cannot meet the needs of practical utilization. Based on this, the present invention starts from the structure of lignin itself, utilizes the characteristics of rich oxygen-containing functional groups, and prepares lignin-based hydrogels that can adsorb anions and cations through free radical polymerization reactions for efficient removal and recovery of nitrogen and phosphorus ions in water bodies, and applies them to the field of rice hydroponics to explore the feasibility of lignin-based hydrogels as slow-release fertilizer carriers. Summary of the invention
[0005] The present invention aims at the deficiencies in the preparation and application of existing nitrogen and phosphorus ion adsorption materials, and provides a preparation method and application of a lignin-based hydrogel that adsorbs nitrogen and phosphorus ions. The present invention uses lignin sulfonate as raw material, methacryloyloxyethyl trimethyl ammonium chloride and acrylic acid as monomers, potassium persulfate as initiator, and N,N-methylenebisacrylamide as cross-linking agent, prepares lignin-based hydrogel through free radical polymerization, and then adsorbs nitrogen and phosphorus ions to obtain lignin-based hydrogel that adsorbs nitrogen and phosphorus ions, and finally applies it to the field of rice hydroponics. The present invention can not only provide a new way for the high-value utilization of industrial lignin, but also the prepared lignin-based hydrogel has a strong adsorption capacity for nitrogen and phosphorus ions in water bodies, and can adsorb nitrogen and phosphorus ions at the same time. In addition, the lignin-based hydrogel after adsorbing nitrogen and phosphorus ions can be developed into a slow-release fertilizer for application in the field of rice hydroponics, and has good application prospects.
[0006] A method for preparing a lignin-based hydrogel for adsorbing nitrogen and phosphorus ions comprises the following steps:
[0007] Step 1: Mix lignin sulfonate and deionized water evenly, then add methacryloyloxyethyl trimethyl ammonium chloride, acrylic acid, N,N-methylenebisacrylamide, and potassium persulfate in sequence, stir evenly, and use nitrogen to remove air to obtain a mixed solution;
[0008] Step 2: transferring the mixed solution obtained in step 1 to a sealed container for free radical polymerization, and soaking the obtained product in deionized water to obtain a lignin-based hydrogel;
[0009] Step 3: Mix the lignin-based hydrogel with an aqueous solution of nitrogen and / or phosphorus ions, and perform adsorption in a shaker. After the adsorption is completed, filter the mixture, and the obtained solid sample is the lignin-based hydrogel after adsorbing nitrogen and phosphorus ions.
[0010] The lignin-based hydrogel for adsorbing nitrogen and phosphorus ions described in the present invention can be divided into three types: the first type is the lignin-based hydrogel for adsorbing nitrogen ions; the second type is the lignin-based hydrogel for adsorbing phosphorus ions; and the third type is the amphoteric lignin-based hydrogel for simultaneously adsorbing nitrogen and phosphorus ions.
[0011] Preferably, the lignin-based hydrogel is an amphoteric lignin-based hydrogel that simultaneously adsorbs nitrogen and phosphorus ions.
[0012] In the above technical solution, the amphoteric fingers in the amphoteric lignin-based hydrogel can adsorb anions and cations at the same time.
[0013] In the method of the present invention, in step 1, the ratio of the lignin sulfonate to deionized water is 0.2 g: 5 to 15 mL.
[0014] Preferably, in step 1, the ratio of the lignin sulfonate to deionized water is 0.2 g:7 mL.
[0015] In the method of the present invention, in step 1, the ratio of the wood sulfonate, methacryloyloxyethyl trimethyl ammonium chloride, acrylic acid, N,N-methylenebisacrylamide and potassium persulfate is 0.2g:1.0-3.0g:1.0-3.0g:0.01-0.05g:0.01-0.05g.
[0016] Preferably, in step 1, the ratio of the lignosulfonate, methacryloyloxyethyltrimethylammonium chloride, acrylic acid, N,N-methylenebisacrylamide and potassium persulfate is 0.2g:2.5g:2.5g:0.03g:0.03g.
[0017] In the method of the present invention, in step 1, the stirring condition is magnetic stirring at 200-600 rpm for 10-30 min.
[0018] In the method of the present invention, in step 2, the free radical polymerization reaction conditions are 40 to 80° C. for 1 to 3 hours.
[0019] Preferably, in step 2, the temperature of the free radical polymerization reaction is 60° C. and the time is 2 hours.
[0020] In the method of the present invention, in step 2, the product is immersed in deionized water for 20 to 40 hours.
[0021] Preferably, the product is immersed in deionized water for 24 hours.
[0022] In the method of the present invention, in step 2, the free radical polymerization reaction is carried out in an oven.
[0023] In the method of the present invention, in step 3, the adsorption conditions are adsorption at 50-150 rpm for 10-600 min at a temperature of 20-40°C.
[0024] Preferably, in step 3, the adsorption condition is 25° C. and 100 rpm for 300 min.
[0025] In the method of the present invention, in step 3, the nitrogen ion aqueous solution is one or more of ammonium chloride solution, ammonium sulfate solution and ammonium nitrate solution.
[0026] In the method of the present invention, in step 3, the aqueous solution of phosphate ions is one or more of a potassium dihydrogen phosphate solution, a dipotassium hydrogen phosphate solution and a sodium dihydrogen phosphate solution.
[0027] Preferably, the nitrogen ion aqueous solution is an ammonium chloride solution.
[0028] Preferably, the aqueous solution of phosphorus ions is a potassium dihydrogen phosphate solution.
[0029] Preferably, the mixed aqueous solution of nitrogen and phosphorus ions is a mixed solution of ammonium chloride solution and potassium dihydrogen phosphate solution.
[0030] In the method of the present invention, in step 3, the concentration of the nitrogen ion aqueous solution is 10 to 200 mg N / L.
[0031] Preferably, the concentration of the nitrogen ion aqueous solution is 100 mg N / L.
[0032] In the method of the present invention, in step 3, the concentration of the phosphate ion aqueous solution is 10 to 200 mg P / L.
[0033] Preferably, the concentration of the phosphate ion aqueous solution is 200 mg P / L.
[0034] In the method of the present invention, in step 3, the nitrogen and phosphorus ion mixed solution is obtained by dissolving ammonium chloride and potassium dihydrogen phosphate in deionized water and stirring the mixture evenly.
[0035] In the method of the present invention, in step 3, the concentration of nitrogen ions in the nitrogen and phosphorus ion mixed solution is 10 to 200 mg N / L, and the concentration of phosphorus ions is 10 to 200 mg P / L.
[0036] Preferably, the concentration of nitrogen ions in the nitrogen-phosphorus ion mixed solution is 100 mg N / L, and the concentration of phosphorus ions is 100 mg P / L.
[0037] In the method of the present invention, the ratio of the lignin-based hydrogel to the nitrogen and / or phosphorus ion aqueous solution is 0.015 g:10-50 mL.
[0038] Preferably, the ratio of the lignin-based hydrogel to the aqueous solution of nitrogen and / or phosphorus ions is 0.015 g:30 mL.
[0039] Another object of the present invention is to provide a lignin-based hydrogel for adsorbing nitrogen and phosphorus ions prepared by the above method.
[0040] Another object of the present invention is to provide the use of the above-mentioned lignin-based hydrogel for adsorbing nitrogen and phosphorus ions as a slow-release fertilizer in the field of rice hydroponics.
[0041] The application of the lignin-based hydrogel adsorbing nitrogen and phosphorus ions as a slow-release fertilizer in the field of rice hydroponics is as follows: freeze-drying the lignin-based hydrogel after adsorbing nitrogen and phosphorus ions and then fully crushing, grinding or mashing it to obtain a slow-release fertilizer, placing it in deionized water to obtain an aqueous solution containing the slow-release fertilizer, dispersing germinated rice seedlings in the aqueous solution, and conducting a rice seedling growth experiment.
[0042] In the above technical solution, the freeze-drying temperature is -50 to -60°C and the time is 40 to 50 hours.
[0043] Preferably, the freeze-drying temperature is -50°C and the time is 48 hours.
[0044] In the above technical solution, the ratio of the lignin-based hydrogel after adsorbing nitrogen and phosphorus ions to deionized water is 0.1 g: 10 to 30 mL.
[0045] Preferably, the ratio of the lignin-based hydrogel after adsorbing nitrogen and phosphorus ions to deionized water is 0.1 g:10 mL.
[0046] In the above technical solution, the germinated rice seedlings are pretreated rice seedlings, and the pretreatment method is: weigh a certain amount of rice seeds, soak them in deionized water for 20 to 40 hours, then scatter 10 to 200 seeds in a pre-wetted culture dish, and culture them at a temperature of 20 to 40° C. and a humidity of 50 to 70% for 1 to 5 days to obtain germinated rice seedlings.
[0047] Preferably, the deionized water soaking time is 48 hours.
[0048] Preferably, 5 to 20 rice seeds are selected for culture, and more preferably 10 seeds are selected.
[0049] Preferably, the rice seeds are cultured at a temperature of 30° C., a humidity of 60%, and a culture time of 7 days.
[0050] In the above technical solution, the rice seedling growth experiment process is: culturing for 5 to 10 days under the environmental conditions of a culture temperature of 20 to 40° C. and a humidity of 50 to 70%.
[0051] Preferably, the rice seedling growth experiment process is: culturing for 7 days under environmental conditions of a culture temperature of 30° C. and a humidity of 60%.
[0052] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0053] 1. The raw material used in the present invention is lignin sulfonate, a by-product of the pulping and papermaking process. This raw material is not only widely available, abundant in reserves, renewable, and environmentally compatible, but also has abundant oxygen-containing functional groups and is suitable for large-scale industrial utilization.
[0054] 2. The hydrogel prepared by the present invention contains abundant nitrogen and phosphorus ion adsorption sites, so it has a strong adsorption capacity for nitrogen and phosphorus ions and can adsorb nitrogen and phosphorus ions at the same time.
[0055] 3. This invention is the first to use lignin hydrogel after adsorbing nitrogen and phosphorus ions in the preparation of slow-release fertilizers. The resulting nitrogen and phosphorus-rich lignin-based hydrogel can be developed into a slow-release fertilizer for use in the field of rice hydroponics.
[0056] 4. The present invention uses industrial lignin to prepare hydrogel, and applies it to the field of nitrogen and phosphorus ion adsorption and slow-release fertilizer. This can not only make full use of lignin, an industrial waste, and provide a new way for its high-value utilization, but also the prepared hydrogel has a strong adsorption capacity for nitrogen and phosphorus ions in water. In addition, the hydrogel after adsorbing nitrogen and phosphorus ions can be used to prepare slow-release fertilizers to promote the growth of rice seedlings. Therefore, it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 The lignin-based hydrogel samples obtained in Examples 1, 2 and 3 are shown.
[0058] Figure 2 The SEM spectra of the lignin-based hydrogels obtained in Examples 1, 2 and 3 at different magnifications.
[0059] Figure 3 The lignin-based hydrogel obtained in Example 1 is NH4 + and H2PO4 - Ion competition adsorption data.
[0060] Figure 4 NH4 is the lignin-based hydrogel obtained in Examples 2 and 3 + and H2PO4 - Ion adsorption data.
[0061] Figure 5 The lignin-based hydrogels obtained in Examples 1, 2 and 3 adsorb NH4 + and H2PO4 - Diagram for promoting the growth of rice seedlings. DETAILED DESCRIPTION
[0062] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0063] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0064] Example 1
[0065] A method for preparing an amphoteric lignin-based hydrogel for adsorbing nitrogen and phosphorus ions comprises the following steps:
[0066] Step 1: 0.2 g of lignin sulfonate and 7 mL of deionized water were mixed to obtain a uniform lignin sulfonate solution, and then 2.5 g of methacryloyloxyethyl trimethylammonium chloride, 2.5 g of acrylic acid, 0.03 g of potassium persulfate and 0.03 g of N,N-methylenebisacrylamide were added in sequence, and magnetic stirring was performed at a speed of 400 rpm for 20 min to completely dissolve the mixture, and air was removed with N2 to obtain a mixed solution;
[0067] Step 2: The mixed solution obtained in step 1 was transferred to a sealed container and placed in an oven at 60°C for 3 h for free radical polymerization. The obtained product was soaked in deionized water for 24 h to obtain lignin-based hydrogel (ALH) (see Figure 1 and Figure 2 ).
[0068] Step 3: Weigh 0.015 g of the ALH hydrogel obtained in step 2 into a 100 mL conical flask, then add 30 mL of a mixed solution of ammonium chloride (100 mg N / L) and potassium dihydrogen phosphate (100 mg P / L) (the preparation method of the mixed solution is: weigh 0.0382 g of ammonium chloride and 0.0439 g of potassium dihydrogen phosphate into 100 mL of deionized water at the same time, mix well to obtain NH4 + Concentration of 100mgN / L and H2PO4 - The conical flask was sealed and placed in a constant temperature shaker, shaken at 25 ° C and 100 rpm for 5 h, and then filtered with a 0.22 μm filter membrane. The solid sample obtained was the lignin-based hydrogel after adsorbing nitrogen and phosphorus ions, recorded as ALH-N&P.
[0069] Effect of lignin-based hydrogel (ALH) on NH4 in water + and H2PO4 - Ion adsorption:
[0070] According to the NH4 + and H2PO4 - The concentration of ions was used to calculate the adsorption amount of nitrogen and phosphorus ions by lignin-based hydrogel (see the results in Figure 3 ), where NH4 + and H2PO4 - The ion concentrations were determined by Nessler's reagent method and ammonium molybdate colorimetric method, respectively.
[0071] Utilize the above-mentioned preparation to absorb NH4 + and H2PO4 - The ionized lignin-based hydrogel (ALH-N&P) was used as a slow-release fertilizer to promote the growth of rice seedlings, including the following steps:
[0072] (1) After freeze-drying (drying at -50°C for 48 h) ALH-N&P hydrogel and ALH hydrogel, 0.1 g of each was weighed and ground thoroughly in a mortar. The resulting solids were then placed in test tubes containing 10 mL of deionized water.
[0073] (2) Weigh a certain amount of rice seeds, soak them in deionized water for 24 hours, and then spread 200 seeds in a pre-wetted culture dish, and culture them for 3 days at a temperature of 30° C. and a humidity of 60%. After the rice seeds germinate, take 10 germinated rice seedlings and spread them in the test tubes obtained in step (1) to carry out a seedling growth experiment;
[0074] (3) Under the conditions of a temperature of 30° C. and a humidity of 60%, the growth of the rice seedlings in step (2) was observed after 7 days, and the stem length, root length, diameter and dry weight of the rice seedlings were measured (the results are shown in Figure 5 and Table 1).
[0075] Example 2
[0076] A method for preparing a lignin-based hydrogel for adsorbing nitrogen ions comprises the following steps:
[0077] Step 1: 0.2 g of lignin sulfonate and 7 mL of deionized water were mixed to obtain a uniform lignin sulfonate solution, and then 2.5 g of methacryloyloxyethyl trimethylammonium chloride, 2.5 g of acrylic acid, 0.03 g of potassium persulfate and 0.03 g of N,N-methylenebisacrylamide were added in sequence, and magnetic stirring was performed at a speed of 400 rpm for 20 min to completely dissolve the mixture, and air was removed with N2 to obtain a mixed solution;
[0078] Step 2: The mixed solution obtained in step 1 was transferred to a sealed container and placed in an oven at 60°C for 3 h for free radical polymerization. The obtained product was soaked in deionized water for 24 h to obtain lignin-based hydrogel (ALH) (see Figure 1 and Figure 2 ).
[0079] Step 3: Weigh 0.015 g of the ALH hydrogel obtained in step 2 into a 100 mL conical flask, and then add 30 mL of ammonium chloride solution (weigh 0.0382 g of ammonium chloride in 100 mL of deionized water to obtain NH4 + The conical flask was sealed and placed in a constant temperature shaker, shaken at 25 ° C and 100 rpm for 5 h, and then filtered with a 0.22 μm filter membrane. The solid sample obtained was the lignin-based hydrogel after adsorbing nitrogen ions, which was recorded as ALH-N.
[0080] Effect of lignin-based hydrogel (ALH) on NH4 in water + Ion adsorption:
[0081] According to the NH4 + The nitrogen ion adsorption capacity of lignin-based hydrogel was calculated based on the concentration of Figure 4 ), where NH4 + The ion concentration was determined by Nessler's reagent method.
[0082] Using the above-prepared adsorbed NH4 + The ionized lignin-based hydrogel (ALH-N) was used as a slow-release fertilizer to promote the growth of rice seedlings, including the following steps:
[0083] (1) After freeze-drying the ALH-N hydrogel (drying at -50°C for 48 h), 0.1 g was weighed and ground thoroughly in a mortar. The resulting solid was then placed in a test tube containing 10 mL of deionized water.
[0084] (2) Weigh a certain amount of rice seeds, soak them in deionized water for 24 hours, then spread 200 seeds in a pre-wetted culture dish, and culture them for 3 days at a temperature of 30° C. and a humidity of 60%. After the rice seeds germinate, take 10 germinated rice seedlings and spread them in the test tubes obtained in step (1) to conduct a seedling growth experiment;
[0085] (3) After culturing for 7 days at a temperature of 30° C. and a humidity of 60%, the growth of the rice seedlings in step (2) was observed, and the stem length, root length, diameter and dry weight of the rice seedlings were measured (the results are shown in Figure 5 and Table 1).
[0086] Example 3
[0087] A method for preparing a lignin-based hydrogel for adsorbing phosphorus ions comprises the following steps:
[0088] Step 1: 0.2 g of lignin sulfonate and 7 mL of deionized water were mixed to obtain a uniform lignin sulfonate solution, and then 2.5 g of methacryloyloxyethyl trimethylammonium chloride, 2.5 g of acrylic acid, 0.03 g of potassium persulfate and 0.03 g of N,N-methylenebisacrylamide were added in sequence, and magnetic stirring was performed at a speed of 400 rpm for 20 min to completely dissolve the mixture, and air was removed with N2 to obtain a mixed solution;
[0089] Step 2: The mixed solution obtained in step 1 was transferred to a sealed container and placed in an oven at 60°C for 3 h for free radical polymerization. The obtained product was soaked in deionized water for 24 h to obtain lignin-based hydrogel (ALH) (see Figure 1 and Figure 2 ).
[0090] Step 3: Weigh 0.015 g of the ALH hydrogel obtained in step 2 into a 100 mL conical flask, then add 30 mL of potassium dihydrogen phosphate solution (weigh 0.0878 g of potassium dihydrogen phosphate into 100 mL of deionized water and mix well to obtain H2PO4 - The conical flask was sealed and placed in a constant temperature shaker, shaken at 25 ° C and 100 rpm for 5 h, and then filtered with a 0.22 μm filter membrane. The solid sample obtained was the lignin-based hydrogel after adsorbing phosphate ions, which was recorded as ALH-P.
[0091] Effect of lignin-based hydrogel (ALH) on H2PO4 in water - Ion adsorption:
[0092] According to the H2PO4 in aqueous solution before and after adsorption - The phosphorus ion adsorption capacity of lignin-based hydrogel was calculated based on the concentration of Figure 3 ), where H2PO4 in the filtrate - The ion concentration was determined by the ammonium molybdate colorimetric method.
[0093] Using the adsorbed H2PO4 prepared above - The ionized lignin-based hydrogel (ALH-P) was used as a slow-release fertilizer to promote the growth of rice seedlings, including the following steps:
[0094] (1) After freeze-drying the ALH-P hydrogel (drying at -50°C for 48 h), 0.1 g was weighed and ground thoroughly in a mortar. The resulting solid was then placed in a test tube containing 10 mL of deionized water.
[0095] (2) Weigh a certain amount of rice seeds, soak them in deionized water for 24 hours, then spread 200 seeds in a pre-wetted culture dish, and culture them for 3 days at a temperature of 30° C. and a humidity of 60%. After the rice seeds germinate, take 10 germinated rice seedlings and spread them in the test tubes obtained in step (1) to conduct a seedling growth experiment;
[0096] (3) Under the conditions of a temperature of 30° C. and a humidity of 60%, the growth of the rice seedlings in step (2) was observed after 7 days, and the stem length, root length, diameter and dry weight of the rice seedlings were measured (the results are shown in Figure 5 and Table 1).
[0097] Table 1. Statistical data of the effects of different treatments of lignin-based hydrogels on the growth of rice seedlings
[0098]
[0099] Figure 1 1 is a picture of the lignin-based hydrogel samples obtained in Examples 1, 2 and 3 of the present invention.
[0100] Figure 2 The SEM spectra of the lignin-based hydrogels obtained in Examples 1, 2 and 3 of the present invention at different magnifications are shown in the figure. It can be seen from the figure that the lignin-based hydrogel has a three-dimensional porous structure of a general dry polymer gel, the distribution of honeycomb pores is relatively regular, and the porous channels and loose network structure on the surface and inside increase the specific surface area of the hydrogel material, which is conducive to exposing more active sites and making the adsorption process easier.
[0101] Figure 3 The lignin-based hydrogel obtained in Example 1 of the present invention is NH4 + and H2PO4 -Ion competition adsorption data. It can be seen from the figure that increasing the NH4 + and H2PO4 - The concentration of ions will lead to a decrease in the equilibrium adsorption amount of another ion by lignin-based hydrogels.
[0102] Figure 4 is the NH4 of the lignin-based hydrogel obtained in Examples 2 and 3 of the present invention + and H2PO4 - Ion adsorption data. It can be seen from the figure that as the amount of lignin-based hydrogel increases from 0.25g / L to 0.50g / L, its adsorption of NH4 + and H2PO4 - The equilibrium adsorption capacity of ions all reached the maximum value.
[0103] Figure 5 The lignin-based hydrogels obtained in Examples 1, 2 and 3 of the present invention adsorb NH4 + and H2PO4 - Table 1 shows the statistical data of the effect of lignin-based hydrogels adsorbing nitrogen and phosphorus ions on the growth of rice seedlings. It can be seen that the dry weight, stem length, diameter and root length of seedlings grown in ALH-N&P, ALH-N and ALH-P were higher than those of seedlings grown in ALH, which proves that the adsorption of NH4 + and / or H2PO4 - The ionic lignin-based hydrogels favored the accumulation of biomass and thus promoted the growth of rice seedlings.
Claims
1. A method for preparing a lignin-based hydrogel for adsorbing nitrogen and phosphorus ions, characterized in that: The following steps are involved: Step 1: Mix lignin sulfonate and deionized water evenly, then add methacryloyloxyethyl trimethyl ammonium chloride, acrylic acid, N,N-methylenebisacrylamide, and potassium persulfate in sequence, stir evenly, and use nitrogen to remove air to obtain a mixed solution; Step 2: transferring the mixed solution obtained in step 1 to a sealed container for free radical polymerization, and soaking the obtained product in deionized water to obtain a lignin-based hydrogel; Step 3: Mix the lignin-based hydrogel with an aqueous solution of nitrogen and / or phosphorus ions, and perform adsorption in a shaker. After the adsorption is completed, filter the mixture, and the obtained solid sample is the lignin-based hydrogel after adsorbing nitrogen and phosphorus ions.
2. The preparation method according to claim 1, characterized in that: In the step 1, the ratio of the lignin sulfonate to deionized water is 0.2 g: 5-15 mL, and the ratio of the lignin sulfonate, methacryloyloxyethyl trimethyl ammonium chloride, acrylic acid, N,N-methylenebisacrylamide, and potassium persulfate is 0.2 g: 1.0-3.0 g: 1.0-3.0 g: 0.01-0.05 g: 0.01-0.05 g.
3. The preparation method according to claim 1, characterized in that: In the step 2, the free radical polymerization reaction conditions are 1 to 3 hours at 40 to 80° C.; and the product is immersed in deionized water for 20 to 40 hours.
4. The method according to claim 1, characterized in that: In the step 3, the adsorption conditions are 20-40° C. at 50-150 rpm for 10-600 min.
5. The method according to claim 1, characterized in that: In step 3, the nitrogen ion aqueous solution is one or more of ammonium chloride solution, ammonium sulfate solution and ammonium nitrate solution; the phosphorus ion aqueous solution is one or more of potassium dihydrogen phosphate solution, dipotassium hydrogen phosphate solution and sodium dihydrogen phosphate solution.
6. The method according to claim 1, characterized in that: In step 3, the concentration of the nitrogen ion aqueous solution is 10 to 200 mg N / L, the concentration of the phosphorus ion aqueous solution is 10 to 200 mg P / L, and the concentration of the nitrogen and phosphorus ion mixed solution is 10 to 200 mg N(P) / L; the ratio of the lignin-based hydrogel to the nitrogen and / or phosphorus ion aqueous solution is 0.015 g:10 to 50 mL.
7. The preparation method according to any one of claims 1 to 6 obtains a lignin-based hydrogel that adsorbs nitrogen and phosphorus ions.
8. Use of the lignin-based hydrogel according to claim 7 as a slow-release fertilizer in the field of rice hydroponics.
9. The use according to claim 8, characterized in that: The lignin-based hydrogel after adsorbing nitrogen and phosphorus ions is freeze-dried and then fully crushed, ground or pounded to obtain a slow-release fertilizer, which is then placed in deionized water to obtain an aqueous solution containing the slow-release fertilizer.
10. The use according to claim 9, characterized in that: The freeze-drying temperature is -50 to -60°C and the time is 40 to 50 hours; the ratio of the lignin-based hydrogel after adsorbing nitrogen and phosphorus ions to deionized water is 0.1 g:10 to 30 mL.
Citation Information
Patent Citations
Preparation method of soil amendment capable of controlling soil erosion
CN102477300A
Production method of bentonite based amphiprotic high-water-retention resin for fertilizer slow release carrier
CN107652442A
Preparation of lignin-based composite hydrogel and application of lignin-based composite hydrogel in heavy metal ion adsorption and luminescent materials
CN113509907A
Preparation method of adsorption type degradable soil moisture preservation slow release fertilizer based on modified wheat straw
CN114920606A
Method for grafting lignin, polymerizates produced according to the method and the utilization thereof
US6593460B1